implicit differentiation
1) y=x^2+yx
2) xy-y^3=1
3) 1/xy-y^2=2
differentiation
1) f(x)=<square root>(x^2-1)/ 1+<square root>(x^2+1)
please find
1) d/dx <square root> f(x)+g(x)
thanks sososososoos much!!!!!!!!!
implicit differentiation
1) y=x^2+yx
2) xy-y^3=1
3) 1/xy-y^2=2
differentiation
1) f(x)=<square root>(x^2-1)/ 1+<square root>(x^2+1)
please find
1) d/dx <square root> f(x)+g(x)
thanks sososososoos much!!!!!!!!!
I'll show you how to do the first example. I leave the following questions for you. I've mentioned above what you should do with the other questions.
to #1: Use product rule with the second summand:
$\displaystyle y=x^2+yx~\implies~ y'=2x+(y+x\cdot y')$
Collect all terms containing y' at the LHS:
$\displaystyle y'-x \cdot y' = 2x+y ~\implies~y'(1-x)=2x+y~\implies~ y'=\dfrac{2x+y}{1-x}$